Structure of the cold-shock domain protein from Neisseria meningitidis reveals a strand-exchanged dimer. - Ren, J; Nettleship, J; Sainsbury, S; Saunders, N; Owens, R (2008)
The structure of the cold-shock domain protein from Neisseria meningitidis has been solved to 2.6 A resolution and shown to comprise a dimer formed by the exchange of two beta-strands between protein monomers. The overall fold of the monomer closely resembles those of other bacterial cold-shock proteins. The neisserial protein behaved as a monomer in solution and was shown to bind to a hexathymidine oligonucleotide with a stoichiometry of 1:1 and a K(d) of 1.25 microM.